Bioactive Metabolites from Indigenous Actinomycetes Isolated from Marine Water - Syed Abdus Subhan,; Abdul Wahab,; Talat Yasmeen Mujahid,; Tanveer Abbas,; Nayyar Mehmood ,; Iqra Ahmed, (Journal of Pharmacy and Nutrition Sciences, 2015)
Microbial natural products have continued to play an important role in the discovery of novel chemicals for the development of important therapeutic agents. Actinomycetes form a potent reservoir of biologically active secondary metabolites and enzymes. The need for finding novel bioactive compounds for the development of new therapeutic agents is required due to the emergence of antibiotic resistance among pathogenic bacteria. Actinomycetes are considered as one of the best producers of variety of antagonistic compounds that could serve as potential chemotherapeutic agents. The present study was undertaken to find new antagonistic compounds from actinomycetes. Actinomycetes were successfully isolated from marine water samples collected at various locations of Karachi. Initially 39 isolates were collected out of which 23 were found to produce active metabolites against one or more test bacterial cultures. Actinomycetes strains IS26, IS33, and IS39 showed significant potential of having bioactive metabolites. Further, the spectrum of those strains was tested against gram positive and gram negative bacteria and results showed variable potential of actinomycetes to inhibit bacterial growth.